The Undergraduate Political Science Curriculum in the University of Dhaka: A Critical Analysis from Integration Perspective - M. Abdul Aziz (Ilmu Inovasi Nusantara, 2022)
It has been evident that the primary objective of university education is to deliver graduates with integrated personalities with the full combination of values and rational, humane, and generic skills. The curriculum always plays the most significant role in building graduates' personalities. In exploring the outcome of the undergraduate program in political science at the University of Dhaka, this research has examined its' curriculum based on a theoretical framework titled 'the Islamic Integrated University Curriculum model (IIUC).' The IIUC model accommodates national philosophy and vision to serve the nation by preparing well-round graduates with four characteristics: the good man, general employability, expertness in discipline, and as a social being. The key criteria for review included the university vision and mission, the program objectives, the structure of the program, the content of the courses, and selected readings of the political science department, which were analyzed in terms of comprehensiveness and contemporary challenges.